Efficacy, Safety, and Patient Satisfaction of a Monophasic Cohesive Polydensified Matrix Versus a Biphasic Nonanimal Stabilized Hyaluronic Acid Filler After Single Injection in Nasolabial Folds. Issue 7 (18th March 2013) - Buntrock, Heike; Reuther, Tilmann; Prager, Welf; Kerscher, Martina
<x xml:space="preserve">Abstract</x> Background Intradermal injection of hyaluronic acid (HA) is currently the criterion standard to reduce the appearance of nasolabial folds (NLF). Objective Effects of a monophasic HA filler using cohesive polydensified matrix (CPM) technology were compared with those of nonanimal stabilized HA (NASHA). Materials and Methods In a double‐blind, half‐side comparison, 20 subjects (ages 35–65, mean 52 ± 5.6) with symmetric NLF grade 3 to 4 were randomized to contralateral treatment with a monophasic polydensified filler (CPM) and a biphasic HA filler (NASHA). Efficacy was assessed at baseline and after 2, 24, and 48 weeks using a wrinkle severity rating scale (WSRS) for NLF, subject questionnaire, and biophysical in vivo methods. Results All subjects showed significant improvements with both fillers up to day 365. Subject questionnaires confirmed significantly less injection pain for the CPMHA, significantly greater patient satisfaction after 2 weeks with both fillers, and after 24 and 48 weeks significantly greater improvement with the CPMHA compared to baseline. WSRS and skin surface topography parameters improved significantly up to 48 weeks with both fillers. Conclusion A single intradermal injection of a monophasic CPMHA and a biphasic NASHA filler showed significant improvements in WSRS and measured wrinkle depth up to 48 weeks for both fillers and significant differences in injection comfort and patient satisfaction in favor of CPMHA.